VALUE OF TRAVEL TIME AND TRAVEL TIME SAVINGS - Turiak, Marek (Doprava a spoje, 2012)
Value of travel time is a concept often disregarded by a general public but is of an increasing importance to business travelers. Value of travel time concept helps in selecting the most cost efficient travel arrangement. This concept is discussed in details providing differences for various types of transport as well as for various groups of passengers.